Students' Motivation in Learning English in Indonesia: A Critical Review - Suryani, Lilis; Widhiyanto, Widhiyanto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Teaching English as a foreign language in Indonesia has grown significantly. English is a prominent discipline at the university level. University students face problems in learning English. Some factors influence the success of learning, and one of them is motivation. Motivation is essential in education, and some research has investigated it. The study has shown that motivation is divided into intrinsic and extrinsic motivation. Hence, this paper aims to critically review students ‘motivation in learning English in higher education in Indonesia. Four articles related to students' motivation were reviewed based on some steps: identifying the topic, the purpose of the study, determining resources, choosing the articles, reviewing the articles, and writing the summary. The results showed that every article found two types of motivation: intrinsic and extrinsic. The student's motivation at each university is different; it can be seen that the result of motivation is different. The most dominant motivation from the four articles is extrinsic motivation. The students’ external factors significantly impact learning. Besides, intrinsic motivation plays important factor too, and it has a good impact on learning. Therefore, identifying the student’s motivation can help the teacher design the teaching method to make successful learning.